Peningkatan Literasi Inklusif Melalui Penerapan Metode Read Aloud di SKH 01 Pandeglang - Ajeng Muliasari; Yeni Sulaeman; Omah Mukarromah; Dede Sri Sukaesih; Reni Suwenti; Yeni Haerani (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2026)
Literacy is a fundamental aspect that must be developed in students with special needs as a provision for learning processes and daily life. However, efforts to strengthen literacy in special schools still face challenges, particularly in adaptive and enjoyable teaching methods. This Community Service Program (PKM) aims to improve inclusive literacy through the application of the Read Aloud method at SKH 01 Pandeglang. The program was carried out through several stages: student needs observation, individual assistance, implementation of Read Aloud, interactive discussion, and evaluation of student participation and response. A total of 15 students with special needs participated, assisted by lecturers and PGSD students. The results showed an increase in reading interest, listening skills, social interaction, and student communication during the learning process. In addition, the program provided practical inclusive education experience for students and broadened teachers' insights regarding adaptive learning strategies. In conclusion, the Read Aloud method is proven to be an effective strategy in supporting the strengthening of literacy for students with special needs and is recommended for adoption in similar educational settings.